IDENTIFIKASI MISKONSEPSI SISWA TENTANG MATERI MAGNET DI SEKOLAH DASAR - Prahasdita, Inggrit Nada; Ngazizah, Nur; Ratnaningsih, Arum (Universitas Tanjungpura, 2025)
AbstractThe purposes of this study are to identify misconceptions among Elementary School students related to the material about magnet taught and to describe the factors causing these misconceptions. The subjects of this study were 18 sixth grade students (7 males and 11 females). This study uses a qualitative descriptive approach. The research data were obtained through observation, documentation, interviews, and 16 multiple-choice tests accompanied by a CRI (Certainty of Response Index) column. The data analysis consisted of data reduction, data presentation, and conclusion drawing. The results of the study reveal that students believe that magnets only attract iron, the type of magnet from nature is artificial, the strongest magnetic force is located in the middle, and there is only one way to make a magnet. Not only that, misconceptions also occur related to students' misunderstanding of the concept of magnetic poles and their misconceptions about the use of magnets in compasses and refrigerators. The causes of misconceptions found are students' low interest in learning both at home and at school, the textbooks used, and the teacher's teaching methods.Keywords: Material About Magnet, CRI Method, Misconceptions. AbstrakTujuan penelitian ini adalah untuk mengidentifikasi miskonsepsi siswa Sekolah Dasar terhadap materi magnet yang diajarkan dan mendeskripsikan faktor penyebab miskonsepsi tersebut. Subjek penelitian ini adalah siswa kelas VI yang berjumlah 18 siswa (7 laki-laki dan 11 perempuan). Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data penelitian diperoleh melalui observasi, dokumentasi, wawancara, dan tes pilihan ganda sebanyak 16 soal yang disertai kolom CRI (Certainty of Response Index). Analisis data terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian mengungkap bahwa siswa meyakini magnet hanya menarik besi, jenis magnet dari alam adalah buatan, gaya magnet yang terkuat terletak pada bagian tengah, dan hanya ada satu cara membuat magnet. Tak hanya itu, miskonsepsi juga terjadi terkait kekeliruan pemahaman siswa akan konsep kutub magnet dan miskonsepsi mereka terhadap penggunaan magnet pada kompas dan lemari es. Penyebab miskonsepsi yang ditemukan yaitu rendahnya minat belajar siswa baik di rumah ataupun di sekolah, buku pembelajaran yang digunakan, dan metode pengajaran guru.Kata Kunci: Materi Magnet, Metode CRI, Miskonsepsi.